Revision of the non-Afrotropical species of Trigastrotheca Cameron (Hymenoptera: Braconidae: Braconinae) with descriptions of four new species - Quicke, Donald L. J.; Butcher, Buntika A.; Ranjith, A. P.; Belokobylskij, Sergey A. (Zootaxa, 2017)
The Asian species of Trigastrotheca are revised. Four species are described as new: T. pariyanonthae sp. nov. from Thailand, T. sureeratae sp. nov. from Thailand, T. luzonensis sp. nov. from the Philippines, and T. maetoi sp. nov. from Indonesia (Kalimantan). Trigastrotheca tridentata (Enderlein) is redescribed and recorded from India for the first time. A key is provided to differentiate all non-Afrotropical species of the genus.